Effect of Kinesio taping on electromyographic activity of leg muscles during gait in children with developmental coordination disorder: A randomized controlled trial. Issue 6 (February 2019) - Yam, Timothy Tsz Ting; Wong, Man Sang; Fong, Shirley Siu Ming
Abstract: Objective: This study aimed to evaluate the effectiveness of Kinesio tape (KT) on lower limb muscle activation pattern in children with developmental coordination disorder (DCD) during walking. Design: A parallel-group randomized controlled trial. Setting: University laboratory setting. Participants: Twenty-five children with DCD were randomly allocated to the KT group (mean age = 7.97 years) and 24 to the control group (mean age = 8.04 years). Intervention: KT group received KT application to the quadriceps and gastrocnemius muscles whereas the control group received no intervention. Measurements: Peak muscle activation (in percentage of maximal voluntary isometric contraction [%MVIC]) in the lower limbs during gait was measured by means of surface electromyography, electrogoniometry, and foot contact switches. Results: Gastrocnemius medialis activation during mid stance (23.46%MVIC, 95% CI = −32.53, −14.39) and late stance phases (3.25%MVIC, 95% CI = −5.67, −0.81) of gait increased after the application of KT in the KT group compared to baseline values. The KT group demonstrated 26.87%MVIC (95% CI = 26.87, 7.11) higher gastrocnemius medialis muscle peak activation during mid stance phase at post-test when compared with the control group. Moreover, gastrocnemius medialis and biceps femoris muscle peak activation during loading response decreased by 8.36%MVIC (95% CI = 2.71, 14.02) and 3.54%MVIC (95% CI = 1.08, 6.01), respectively, in the control group overtime. Conclusions: The application of KT on children with DCD had an increased gastrocnemius medialis muscle activation during stance phase. KT could be incorporated into gait re-education programmes to facilitate muscle contraction in these children.